Fostering regional cooperation and integration for recovery and resilience guidance note (COVID-19 in Asia and the Pacific guidance notes)
The publication identifies opportunities for regional cooperation and integration to complement national efforts in fostering an inclusive, sustainable, and resilient recovery. Cooperation can be widened to include regional health security, trade in ICT-enabled services, and financial safety nets. It can be deepened to reach more stakeholders and sectors. It can also become more open through flexible collaboration beyond existing subregional frameworks and greater sharing of knowledge and expertise.